2013
DOI: 10.2174/1567205011310080011
|View full text |Cite
|
Sign up to set email alerts
|

A Resurrection of 7-MEOTA: A Comparison with Tacrine

Abstract: Alzheimer´s disease (AD) is a progressive neurodegenerative dementia which currently represents one of the biggest threats for the human kind. The cure is still unknown and various hypotheses (cholinergic, amyloidal, oxidative, vascular etc.) are investigated in order to understand the pathophysiology of the disease and on this basis find an effective treatment. Tacrine, the first approved drug for the AD disease treatment, has been reported to be a multitargeted drug, however it was withdrawn from the market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 0 publications
2
61
0
1
Order By: Relevance
“…However, compounds 1 and 2 inhibited AChE in comparable concentrations to those acting on the nicotinic receptor; whereas 7-MEOTA and compound 3 needed to be administered at higher concentrations to inhibit AChE. Moreover, 7-MEOTA has been evaluated previously, concerning how it influences the neuronal α4β2 nicotinic receptor (Soukup et al 2013). 7-MEOTA interacts slightly more effectively with muscular than neuronal nAChR (IC 50 = 4 µmol/l, respectively 15 µmol/l).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, compounds 1 and 2 inhibited AChE in comparable concentrations to those acting on the nicotinic receptor; whereas 7-MEOTA and compound 3 needed to be administered at higher concentrations to inhibit AChE. Moreover, 7-MEOTA has been evaluated previously, concerning how it influences the neuronal α4β2 nicotinic receptor (Soukup et al 2013). 7-MEOTA interacts slightly more effectively with muscular than neuronal nAChR (IC 50 = 4 µmol/l, respectively 15 µmol/l).…”
Section: Discussionmentioning
confidence: 99%
“…Except for compound 2, the drugs showed similar penetration abilities as the parent compound 7-MEOTA (Tab. 3), which has been proved to cross BBB (Soukup et al 2013). Donepezil, which was used as a model of a CNS-permeable drug, confirmed an adequate experimental setup by its high penetration rate (87%).…”
Section: Bbb Penetration Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Computational studies performed about twenty years ago by Pang et al 14 tested the strategy of a double interaction of an inhibitor with the enzyme. 38 The authors found that methylene chain spacers joining two units of tacrine moiety allowed a double interaction of the compound with the enzyme by binding simultaneously to the CAS and PAS. 14,[38][39][40] These results lead the authors to perform the synthesis of alkylene-linked bis-tacrine compounds (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…38 The authors found that methylene chain spacers joining two units of tacrine moiety allowed a double interaction of the compound with the enzyme by binding simultaneously to the CAS and PAS. 14,[38][39][40] These results lead the authors to perform the synthesis of alkylene-linked bis-tacrine compounds (Figure 1). 40 Among the compounds obtained, the heptylene-linked bis-tacrine (2), also called bis(7)-cognitin or bis(7)-tacrine was found to be almost fifteen hundred times more potent against AChE than tacrine.…”
mentioning
confidence: 99%